Looking back and abroad while (not) moving forward. Migration, ideas and the stability of citizenship in Spain - Pasetti, Francesco; Schweitzer, Reinhard (Frontiers in Sociology, 2025)
This article addresses the remarkable stability of the Spanish citizenship regime. Since it was established in 1982, it has remained largely unchanged, despite the country's rapid transformation from a country of emigration to a major destination for non-EU immigrants. We complement existing explanations for this phenomenon by shifting the analytical focus to the realm of ideas. Based on a close analysis of the law-making process and parliamentary debates about citizenship reforms between 1978 and 2024, we argue that this puzzling stability can partly be attributed to the widely shared and remarkably stable way in which the country's political elite conceives nationality. We identify three constitutive elements that make this dominant citizenship frame: (i) the preference for blood-ties over territorial presence, (ii) the preferential treatment of emigrants (and their descendants) over immigrants, and (iii) the predilection for potential citizens' historical over contemporary connections to Spain. This set of ideas, in which political parties' views overlap, has constituted the tracks along which the country's nationality laws have evolved. It has outlived not only demographic but also political changes including the appearance of the country's first far-right, anti-immigrant party. By focusing on ideas, this article offers a new analytical and less deterministic perspective, complementing the explanatory backdrop provided to date by the scholarship concerned with citizenship law-making. Our findings and analysis contribute to a fuller understanding of the politics of citizenship in Spain and—more generally—of the ambiguous role that past, present, and future migratory dynamics (can) play in shaping—the evolution of citizenship law-making. It thereby also contributes to the literature on the multifaceted nexus between citizenship and migration and to broader debates on the importance of ideas in public policymaking.